Lipoproteins are an important bacterial component responsible for bone destruction through the induction of osteoclast differentiation and activation. (18th October 2013) - Kim, Jiseon; Yang, Jihyun; Park, Ok‐Jin; Kang, Seok‐Seong; Kim, Woo‐Shin; Kurokawa, Kenji; Yun, Cheol‐Heui; Kim, Hong‐Hee; Lee, Bok Luel; Han, Seung Hyun
ABSTRACT Bacterial infection can cause inflammatory bone diseases accompanied by the bone destruction resulting from excess generation of osteoclasts. Although lipoproteins are one of the major immunostimulating components of bacteria, little is known about their effects on bone metabolism. In this study, we investigated the role of lipoproteins in bacteria‐induced bone destruction using Staphylococcus aureus wild type, its lipoprotein‐deficient mutant, and synthetic lipopeptides Pam2CSK4 and Pam3CSK4 known to mimic bacterial lipoproteins. Formaldehyde‐inactivated S. aureus or the synthetic lipopeptides induced severe bone loss in the femurs of mice after intraperitoneal administration and in a calvarial bone implantation model, whereas the lipoprotein‐deficient S. aureus did not show such effects. Mechanism studies further identified three action mechanisms for the lipopeptide‐induced osteoclast differentiation and bone resorption via (i) enhancement of osteoclast differentiation through Toll‐like receptor 2 and MyD88‐dependent signaling pathways; (ii) induction of pro‐inflammatory cytokines, TNF‐α and IL‐6; and (iii) upregulation of RANKL expression with downregulation of osteoprotegerin expression in osteoblasts. Taken together, these results suggest that lipoprotein might be an important bacterial component responsible for bone destruction during bacterial infections through augmentation of osteoclast differentiation and activation. © 2013 American Society for Bone and Mineral Research.